Nanotechnology in Clothing and Fabrics - Muralidharan Paramsothy (Nanomaterials, 2021)
Making clothing and fabric with nanoparticles or nanofibers allows the improvement of fabric properties without a significant increase in weight, thickness, or stiffness [...]